2022
DOI: 10.22236/j.bes/629575
|View full text |Cite
|
Sign up to set email alerts
|

PBL Assisted with Al-Quran Integrated Audio Visual Media: Its Effect on Student Learning Outcomes on Reproductive System Materials

Abstract: Background: Learning outcomes are the object of class evaluation as new abilities obtained by students after participating in the learning process. However, the facts on the ground show that high school students' learning outcomes in biology material are still low. Based on the results of interviews with State Madrasah Aliyah teachers in Serdang Bedagai, students' learning outcomes are generally low because they do not have a strong understanding of concepts, one of which is the material on the reproductive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Various studies have shown the effectiveness of different learning media in enhancing students' cognitive learning outcomes in biology subjects related to the reproductive system (Eliana et al, 2022;Ibrahim, 2023;Kurniawan et al, 2018;Panjaitan et al, 2020;Roihana et al, 2018). The integration of audio-visual media, such as Al-Quran integrated audio visual media, has also been shown to have a positive impact on student learning outcomes in reproductive system materials (Aglillah & Jayanti, 2022). Moreover, employing video and flashcards as instructional tools proves efficacious in enhancing student engagement and academic achievements in the human reproductive system (Roihana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the effectiveness of different learning media in enhancing students' cognitive learning outcomes in biology subjects related to the reproductive system (Eliana et al, 2022;Ibrahim, 2023;Kurniawan et al, 2018;Panjaitan et al, 2020;Roihana et al, 2018). The integration of audio-visual media, such as Al-Quran integrated audio visual media, has also been shown to have a positive impact on student learning outcomes in reproductive system materials (Aglillah & Jayanti, 2022). Moreover, employing video and flashcards as instructional tools proves efficacious in enhancing student engagement and academic achievements in the human reproductive system (Roihana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%